Rugose corals at the Tournaisian–Viséan transition in the Central Taurides (S Turkey) – Palaeobiogeography and palaeoceanography of the Asian Gondwana margin. (February 2015) - Denayer, Julien
Graphical abstract: Highlights: The first taxonomic description of rugose corals from Central Taurides is given. Four stratigraphical assemblages are recognized at Tournaisian–Viséan transition. The palaeobiogeographic and dispersion patterns of rugose corals are discussed. Abstract: This paper gives the first taxonomic description of the Upper Tournaisian–Lower Viséan rugose coral fauna of the Yaricak Formation (Aladag Unit, Central Taurides, South Turkey). Fifteen species belonging to twelve genera were identified, one species is newly described: Eokoninckocarinia gemmina . The corals are stratigraphically distributed in four assemblages. The two typical assemblages of the Upper Tournaisian are composed of widely distributed taxa ( Uralinia, Caninia, Proheterelasma, Zaphrentites ). The assemblage crossing the Tournaisian–Viséan boundary is characterized by Eurasian and cosmopolitan and widely distributed taxa ( Calmiussiphyllum, Siphonophyllia, Bifossularia Amygdalophyllum, Caninophyllum, Keyserlingophyllum ) and Asian taxa ( Kueichouphyllum ). The youngest assemblage, dominated by Eokoninckocarinia gemmina sp. nov., has yielded foraminifers Moliniacian (Lower Viséan) in age. These assemblages form a low diversity level-bottom community which is typical of the South Palaeotethys ' Kueichouphyllum Zone' extending along the Asian margin of Gondwana (Cimmerian Terrane) during Lower Carboniferous times. As in the other Cimmerian blocks, all the corals are solitary and colonial taxa are virtually absent. This absence is tentatively explained by the high palaeolatitude (c. 50°S) position of the Cimmerian Terrane in the southern part of the Palaeotethys Ocean for this time slice. A cold-water palaeo-current running eastward along the Gondwana margin might also be considered as it possibly could explain the wide distribution of the Kueichouphyllum fauna, restricted east of Africa in the southern coast of the Palaeotethys. Palaeoceanography, palaeoclimate and facies issues are discussed as possible causes of the diversity gradient observed between the eastern (Australia, Malaya) and the western (North Africa) margin of the Gondwana.